Past abrupt climate change - Riechers, Keno (Technical University of Munich, 2024)
This thesis investigates a series of past abrupt climatic changes, the last glacial‘s Dansgaard–Oeschger events, from a dynamical systems perspective. This is complemented by direct Bayesian inference from paleoclimate proxy records to the actual course of these events. The results provide important insights for understanding nonlinear effects in the dynamics of the climate system. Diese Dissertation erforscht eine Serie vergangener abrupter Klimaveränderungen, die Dansgaard-Oeschger Ereignisse des letzten Glazials, aus der Perspektive dynamischer Systeme. Diese wird ergänzt durch direkte Inferenz aus paläoklimatischen Proxy-Zeitreihen hinsichtlich des tatsächlichen Verlaufes der Ereignisse. Die Ergebnisse liefern wichtige Erkenntnisse für das Verständnis nicht-linearer Effekte in der Dynamik des Klimasystems, welche zentral für die Existenz klimatischer Kipppunkte sind.